2009
DOI: 10.1155/2009/657369
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccine by Fusions of Dendritic and Cancer Cells

Abstract: Dendritic cells (DCs) are potent antigen-presenting cells and play a central role in the initiation and regulation of primary immune responses. Therefore, their use for the active immunotherapy against cancers has been studied with considerable interest. The fusion of DCs with whole tumor cells represents in many ways an ideal approach to deliver, process, and subsequently present a broad array of tumor-associated antigens, including those yet to be unidentified, in the context of DCs-derived costimulatory mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 125 publications
(155 reference statements)
0
22
0
Order By: Relevance
“…116 Examples of immunotherapy include therapeutic vaccination with synthetic peptides, proteins, cell lysates, RNA, and necrotic or apoptotic tumor cells. 117 T cells derived from vaccination with synthetic or modified peptides have thus far resulted in T cells with poor cytolytic function, however the delivery of protein involving endogenous antigen processing and epitope selection results in superior antigen presentation and improved immune responses. Unfortunately, a large number of immunotherapeutic approaches use single antigens or peptides to elicit antigen-specific immune responses.…”
Section: Peptide and Protein Cargomentioning
confidence: 99%
“…116 Examples of immunotherapy include therapeutic vaccination with synthetic peptides, proteins, cell lysates, RNA, and necrotic or apoptotic tumor cells. 117 T cells derived from vaccination with synthetic or modified peptides have thus far resulted in T cells with poor cytolytic function, however the delivery of protein involving endogenous antigen processing and epitope selection results in superior antigen presentation and improved immune responses. Unfortunately, a large number of immunotherapeutic approaches use single antigens or peptides to elicit antigen-specific immune responses.…”
Section: Peptide and Protein Cargomentioning
confidence: 99%
“…The strategy for DC/tumor fusion vaccine is based on the fact that DCs are the most potent antigen-presenting cells in the body, whereas tumor cells express abundant tumor antigens. In animal studies, DC/tumor fusion vaccines have been shown to possess the elements essential for processing and presenting tumor antigens to host immune cells, for inducing effective immune response, and for breaking T-cell tolerance to TAAs (Gong, Chen et al, 1997;Koido, Hara et al, 2007;Gong, Koido et al, 2008;Koido, Hara et al, 2009;Koido, Hara et al, 2010a;Koido, Homma et al, 2010b). Recently, we have reported that fusions of human pancreatic cancer cells and DCs induce CTL responses against pancreatic cancer cells in vitro (Koido, Hara et al, 2010a).…”
Section: Dc-based Vaccinesmentioning
confidence: 99%
“…Moreover, this rich source of antigens contains epitopes of both CD8+CTLs and CD4+ T helper cells (Koido, Hara et al, 2005;Koido, Hara et al, 2009;Koido, Homma et al, 2010c). Thus, whole tumor cells could greatly diminish the chance of tumor escape compared to using single epitope peptide vaccines.…”
Section: Whole Tumor Cell-based Vaccinesmentioning
confidence: 99%
“…DCs are potent antigen-presenting cells playing a main role in the initiation and regulation of primary immune responses. The fusion of DCs with tumor cells represents a perfect strategy to deliver, process, and present a broad array of tumor-associated antigens, including unknown tumor antigens, in the context of DCs-derived co-stimulatory molecules (58). With the transduction of IL-12 and IL-18 genes into the fusion cells (fusion/IL-12/IL-18), five times increase was observed in the level of IFN-γ.…”
Section: Thementioning
confidence: 99%